Solar Power Technologies and Prospective Utilisation of Solar Energy in Kerala: A Techno-Economic Analysis in the Background of Energy Crisis. - Liji Samuel and Prasad A. K (International Journal of Research and Analytical Reviews, 2018)
Solar power incident on the earth’s surface chiefly depends on parameters like topographical location, earth-sun movements andangle of the earth’s rotational axis. Solar power is derived directly from the sun`s natural light and its use is both environment-friendly and cost-effective over the long term. Solar power can be used to generate electricity to homes, business and industrial structure.For the last few years, the State faces power crises.The rising power demand supply mismatch the reaping of solar power is the only solution. Kerala, which is situated in Malabar Coast developing a part of western coast of India. Which receives an annual average solar insolation over 5.5 KWh/sq.m/day.Kerala has very good renewable energy policies for different solar power harvesting methods such as roof top solar photovoltaic plants,off grid solar plants, decentralized wind-solar -hybrid plants etc.